Metabolic Syndrome in Patients with Rheumatoid Arthritis - Ayla Akbal; Barın Selçuk; Aysel Gürcan; Aydan Kurtaran; Murat Ersöz; Müfit Akyüz (Archives of Rheumatology, 2009)
Objective: The aim of this study was to investigate the prevalence of metabolic syndrome (MS) and components of MS and to evaluate the relation between MS and functional state in patients with RA. Material and Methods: A total of 138 patients (71 with rheumatoid arthritis, 67 controls) were included in this study. The diagnosis of rheumatoid arthritis was made according to the criteria of the American College of Rheumatology (ACR) for Rheumatoid Arthritis, and the diagnosis of MS was made according to the diagnostic criteria of the American Medical Association Summary of the National Cholesterol Education Program Adult Treatment Panel III Report (NCEP ATP III). The functional status of patients was determined according to Steinbrocker functional classification. Results: MS was found in 28 (28.4% and 16% in rheumatoid arthritis patients and control group, respectively). No differences between these two groups were determined. According to Steinbrocker functional classification, 93% of cases with rheumatoid arthritis were in stage 1 or stage 2. Systolic blood pressure levels and triglycerides were found significantly higher in patients with rheumatoid arthritis. No differences among the other MS components were determined. Although the fasting blood glucose levels and erythrocyte sedimentation rates were found higher in the patients that had been using corticosteroids, this use of the drug did not cause any significant increase in MS prevalence. Conclusion: Although the systolic blood pressure levels and triglyceride levels were found higher in patients with rheumatoid arthritis, no differences in the prevalence of MS between the two groups was determined. A positive correlation between prevalence of MS and worsening of functional status was found in patients with RA. (Turk J Rheumatol 2009; 24: 202-5)